Pengaruh Penerapan PBL Terintegrasi Kooperatif Jigsaw terhadap Sikap dan Hasil Belajar Peserta Didik Kelas IX SMPN 1 Pallangga - Sitti Aisyah; Firdaus Daud; Muhammad Danial (UNM Journal of Biological Education, 2022)
This study aims to determine the effect of implementing jigsaw integrated PBL on students' attitudes and learning outcomes. The method used is descriptive and inferential analysis method. In this study, there are three attitude indicators studied, namely: cognitive, affective, and conative. The indicator of learning outcomes studied is the cognitive aspect. The population of this study was the entire class IX class of SMPN 1 Pallangga, totaling 11 classes for the 2021/2022 academic year on the subject of inheritance. The experimental class was taught using the jigsaw cooperative integrated PBL learning model and the control class using the PBL learning model. Class IX.7 was chosen as the experimental class with 16 students and class IX.5 as the control class with 16 students. Sampling was done randomly to determine the sample class from the population. The instrument used was a Likert model of science learning attitude questionnaire, and a multiple-choice learning outcome test. The results of the research and data analysis showed that there was an effect of implementing the integrated jigsaw PBL on the attitudes and learning outcomes of science students in class IX SMPN 1 Pallangga.